Kabinet Drees. Zittend links: Luns, in het midden Drees en rechts Cals. Staand links achter Drees met sigaret: Mansholt
Kabinet Drees. Zittend links: Luns, in het midden Drees en rechts Cals. Staand links achter Drees met sigaret: Mansholt.